Handbook of Service Science - Maglio, Paul P.; Kieliszewski, Cheryl A.; Spohrer, James C.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Traditional service sectors encompass a wide variety of industries ranging from transportation, retail and healthcare to entertainment, banking, and insurance. As the service sector expands into the global economy, a new science of service is emerging, one that is dedicated to encouraging service innovation by applying scientific understanding, engineering discipline, and management practice to designing, improving, and scaling service systems. This seminal reference considers Service Science to be the study of value co-creation, and finds abundant common elements and themes, common concerns and approaches that converge on this central, real-world phenomena. Handbook of Service Science takes the first major steps to clarifying the definition, role, and future of this nascent field. Incorporating work by scholars from across the spectrum of service research, the volume presents multidisciplinary perspectives on the nature and theory of service, on current research and practice in design, operations, delivery, and innovation of service, and on future opportunities and potential of service research. Handbook of Service Science provides a comprehensive reference suitable for a wide-reaching audience including researchers, practitioners, managers, and students who aspire to learn about or to create a deeper scientific foundation for service design and engineering, service experience and marketing, and service management and innovation. List of contributors includes: Melissa A. Akaka.- John Bailey.- Guruduth Banavar.- Rahul C. Basole.- William J. Baumol.- Gaurav Bhalla.- Mary Jo Bitner.- Jeannette Blomberg.- David E. Bowen.- John R. Bryson.- Richard B. Chase.- Henry Chesbrough.- Eng K. Chew.- Daniel Connors.- Peter W. Daniel.- Andrew Davies.- Faridah Djellal.- Bo Edvardsson.- Shelley Evenson.- Ray P. Fisk.- Faïz Gallouj.- Susanne Glissmann.- Robert J. Glushko.- Michael Gorma.- Michael Gregory.- Dwayne D. Gremler.- Steve J. Grove.- Gerhard, Gudergan.- Evert Gummesson.- Anders Gustafsson.- Alan Hartman.- James L. Heskett.- Kazuyoshi Hidaka.- Barbara Jones.- Uday S. Karmarkar.- Per Kristensson.- Robert F. Lusch.- Linda Macaulay.- Richard Metters.- Ian Miles.- Aleksandra Mojsilovic.- Claire Moxham.- Rogelio Oliva.- Lakshmish Ramaswamy.- Guangjie Ren.- William B. Rouse.- Roland T. Rust.- Scott E. Sampson.- Pamela Samuelson.- Jorge Sanz.- W. Earl Sasser Jr.- Benjamin Schneider.- Carl J. Schramm.- John D. Sterman.- Stephen L. Vargo.- Lars Witell.- Valarie Zeithaml.- Anatoly Zherebtsov
Context: Origins -- Revisiting Where Does the Customer Fit in a Service Operation? -- The Service Profit Chain -- Winning the Service Game -- Customer Equity -- Service Worldsservice worlds -- Context: Theory -- The Unified Service Theory -- Advancing Service Scienceservice science with Service-Dominant Logicservice-dominant logic -- Toward a Science of Service Systems -- Research and Practice: Design -- Technology s Impact on the Gaps Model of Service Quality -- Seven Contexts for Service System Design -- Business Architectures for the Design of Enterprise Service Systems -- A Service Practice Approach -- Research and Practice: Operations -- The Neglect of Service Scienceservice science in the Operations Management Field -- Death Spirals and Virtuous Cycles -- Service Scienceservice science -- Service Engineering -- Research and Practice: Delivery -- The Industrializationindustrialization of Information Services -- Workforce Analytics for the Services Economy -- Understanding Complex Product and Service Delivery Systems -- A Formal Model of Service Delivery -- Research and Practice: Innovation -- ServiceInnovationinnovation -- InnovationInnovation in Services and EntrepreneurshipEntrepreneurship -- Service Innovationservice innovation and Customer Co-development -- Advancing Services Innovation service innovation -- What Effects Do Legal law/legal Rules Have on Service Innovation innovation ? -- Future -- The Future of Service Is Long Overdue -- The Evolution and Future of Service -- Trading zones, Normative Scenarios, and Service Scienceservice science -- The Cambridge-IBM SSMESSME White Paper Revisited -- Service Scienceservice science , Management, and Engineering SSME (SSME) in Japan -- Innovationinnovation and Skills.
Keywords: Economics; Information Systems; Industrial management; Operations research; Management information systems; Economics/Management Science; Operation Research/Decision Theory; Management/Business for Professionals; Business Information Systems; Management of Computing and Information Systems